Effect of Plywood Retrofit on Dynamic Response of URM House subjected to Forced Vibration - Abdul Razak, Abdul Karim; Oyarzo-Vera, Claudio; Norazzlina, M.Sa'don; Ingham, Jason M. (New Zealand Society for Earthquake Engineering, 2009)
The results of non-destructive forced vibration tests on a small-scale unreinforced masonry (URM) house are presented. The main aim of the study was to assess the changes in system level response between the as-built and retrofitted structure. This includes assessment of diaphragm response, wall-diaphragm connection details, in-plane wall response, out-of-plane wall response, and the response of wall corners. Further, the test protocols were designed to investigate two types of retrofit techniques consisting of a plywood diaphragm retrofit and wall-diaphragm connection retrofit. However, this paper only presents the results of plywood retrofit as the experimental study is still in progress. From the results, it was found that the basic dynamic properties (natural frequency and mode shapes) and the force path of the as-built structure were significantly affected after applying the plywood retrofit.